Institutional Durability of Delivery Units in Indonesia: Preliminary Findings: Ketahanan Kelembagaan Unit Kerja Presiden di Indonesia: Temuan Awal (Journal of Political Issues, 2026)
This study examines the dynamics and institutional durability of various delivery units in Indonesia, including the Presidential Work Unit and the Presidential Staff Office, within a comparative cross-administrative framework and the conceptual lens of deliverology, as practiced by the Prime Minister’s Delivery Unit in the United Kingdom. In contrast to short-term approaches driven by leadership style and performance orientation, this study emphasizes the importance of systematizing and sustaining coordination, synchronization, and control functions. The findings reveal that establishing delivery units in Indonesia tends to be temporary and pragmatic, lacking robust legal foundations and strong institutional integration. Political factors, leadership personalization, and overlapping authorities emerge as key impediments. Employing a collective or multiple-case study design with a comparative analytical approach, this research concludes that while several principles of deliverology, such as using targets and performance monitoring, have been adopted, delivery units have yet to be institutionalized as long-term governance instruments. Therefore, the study recommends establishing a stronger legal framework, developing adaptable institutional designs, and promoting professional leadership to ensure the continuity of these units in supporting the implementation of national priority policies.
Keywords: Delivery Unit; Institutional Durability; Presidential Leadership